Attitude and influencing factors of patients with schizophrenia toward long-acting injections: A community-based cross-sectional investigation in China - Sun, Yiying; Tong, Jie; Feng, Ying; Fang, Haiping; Jiang, Tao; Zhao, Liping; Wang, Qiang; Yang, Yi (Frontiers in Public Health, 2022)
Background Low prescription rates of antipsychotic long-acting injections (LAIs) may be a major challenge in the prevention and treatment of schizophrenia. However, there are few studies on the usage and attitude toward LAIs among community-based patients with schizophrenia. Methods A large community-based cross-sectional investigation was conducted among 6,336 patients with schizophrenia from Shanghai, China from March 1 to June 30, 2021. The structured Attitude and Status toward Treatment of Community Patients with Schizophrenia Questionnaire (AST-CSQ) was used to investigate the attitude and influencing factors of community-dwelling patients with schizophrenia toward LAIs. Results Among the 6,336 participants, the average age was 49.28 ± 11.23. The rate of agreement to LAI antipsychotics among participants was 3.16% (n = 200). The family financial resources, care ability, and disease course of the LAIs group were less than those of the non-LAIs group. However, the LAIs group had higher immediate family guardianship, social activity, previous hospitalization, number of hospitalization, outpatient adherence, previous antipsychotic use, antipsychotic adherence, and attitude toward oral antipsychotics than the non-LAIs group, with significant differences between the two groups (p < 0.05). Furthermore, age (β = −0.036, OR 0.964, 95% CI 0.947–0.982), marital status (β = 0.237, OR 1.267, 95% CI 1.002–1.602), care ability (β = 0.709, OR 2.032, 95% CI 1.437–2.875), outpatient adherence (β = −0.674, OR 0.510, 95% CI 0.358–0.725), antipsychotic adherence (β = 0.920, OR 2.509, 95% CI 1.092–5.764), and attitude toward oral antipsychotics (β = −1.357, OR 0.258, 95% CI 0.103–0.646) were significant predictors of attitude toward LAI antipsychotics (p < 0.05). Conclusions The community-dwelling patients with schizophrenia in China had a low willingness to use LAIs. Patients of a younger age, more hospitalizations, and a shorter course of disease were prone to be more willing to accept LAIs. The patients' age, marital status, care ability, outpatient adherence, antipsychotic adherence, and attitude toward oral antipsychotics were important predictor of patients' attitudes toward LAIs. Under the global deinstitutionalized management model of mental disorders, these results highlight an urgent problems for public mental health service providers and policy-makers and provide more solutions for them.